Предмет: Алгебра,
автор: AzaClark
Алгебра.Упростить.
Прошу помочь.
Приложения:
Ответы
Автор ответа:
0
( (2ху (х+3у)(х-3у) - у (х-3у) ) : у² (х²+3ху)=
(2ху -ху - 3у²) (х+3к)(х-3у) : у² (х²+3ху) =
у ( х-3у) (х+3у)(х-3у) * х (х+3у) у² = х у
(2ху -ху - 3у²) (х+3к)(х-3у) : у² (х²+3ху) =
у ( х-3у) (х+3у)(х-3у) * х (х+3у) у² = х у
Похожие вопросы
Предмет: Русский язык,
автор: 12345673079
Предмет: Математика,
автор: elenagrigoreva565
Предмет: Английский язык,
автор: zadrog000
Предмет: Биология,
автор: Ann1282